Peran sosial perpustakaan di era digital native - Triana Santi (UIN Sumatera Utara, 2016)
Library is one unit in an educational institution that has a role to support learning, research, publications by providing various kinds of information in accordance with the needs users. Along with the rapid development of information and communications technology, users today has changed radically. Starting from their behavior in searching for information by utilizing the Internet, the way they learn while playing games or listening to music as well as their pleasure in collaborating and sharing information through networking. They are referred to as the digital natives generation. Key words : Library, Digital Native